'Masters of your fate and the captains of your soul': media representations of the 2018 Invictus Games. Issue 7 (18th June 2021) - English, Peter; Kean, Bridie; Pearce, Simone; Peters, Timothy; Kirby, Katy; Calder, Angela
Abstract: The Invictus Games was established by Prince Harry in London in 2014 and Sydney hosted the fourth version in 2018. Due to the profile of Prince Harry and the growth of the Games, the media has played a major role in delivering news and information about the event and its competitors, as well as highlighting broader themes of rehabilitation and inclusion. This descriptive study investigates the media coverage of the 2018 Invictus Games to identify key narratives underpinning the representations of the event. This paper employs a quantitative and qualitative content analysis to examine similarities and differences in reporting from four Australian media organisations across print, online and television. The findings are based on the examination of 176 articles and more than eight hours of television and multimedia content. The results highlight a greater focus on the event, as well as celebrity and entertainment elements, than those who were competing.